Effects of Physical Training on Physical and Psychological Parameters in Individuals with Patella Tendinopathy: A Systematic Review and Meta-Analysis - Marc Niering; Thomas Muehlbauer (MDPI AG, 2021)
The effectiveness of physical training on physical and psychological parameters in individuals with patella tendinopathy has not been investigated in a systematic review and meta-analysis. The aim of the present study was to determine the effects of physical exercise interventions for measures of physical and psychological performance in subjects with patella tendinopathy. A computerised systematic literature search was conducted in the electronic databases PubMed, Medline, and Web of Science from January 1960 to July 2020. Initially, 506 articles were identified for review of which eleven articles met the inclusion criteria. Our results revealed a small effect (weighted mean standardized mean difference (SMD) = 0.12; nine studies) of physical training on the psychological measure Victorian Institute of Sport Assessment-Patellar tendon scale and a medium effect (weighted mean SMD = 0.61; five studies) on the psychological measure visual analogue scale-both in favour of the intervention group. In contrast, a small effect (weighted mean SMD = −0.05; two studies) in favour of the control group was detected for the physical measure muscle power. Compared to the control condition, physical training seems to be an effective means to improve psychological but not physical parameters in individuals with patella tendinopathy; although conclusions on the latter could have been biased by the small amount of eligible studies (n = 2). In addition, the predetermined cut-off value of ≥6 for the Physiotherapy Evidence Database scale score (i.e., assessment of methodological quality) was only achieved by six out of eleven studies. Thus, further research of high methodological quality is needed to verify whether there is or is not an effect of physical training on physical parameters in persons with patella tendinopathy.